2014
DOI: 10.5194/acp-14-9137-2014
|View full text |Cite
|
Sign up to set email alerts
|

Ozone vegetation damage effects on gross primary productivity in the United States

Abstract: Abstract. We apply an off-line process-based vegetation model (the Yale Interactive Terrestrial Biosphere model) to assess the impacts of ozone (O3) vegetation damage on gross primary productivity (GPP) in the United States during the past decade (1998–2007). The model's GPP simulation is evaluated at 40 sites of the North American Carbon Program (NACP) synthesis. The ecosystem-scale model version reproduces interannual variability and seasonality of GPP at most sites, especially in croplands. Inclusion of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
105
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(117 citation statements)
references
References 62 publications
12
105
0
Order By: Relevance
“…They find the effect to be largest (and positive) at noontime under cloudless conditions, but less over croplands than over forests due to a lower leaf area index (LAI) in these regions. Previous studies have also looked at how ozone and/or PM impact natural vegetation and the carbon cycle, often by incorporating more advanced canopy or leaf-scale process modeling (Strada and Unger, 2016;Yue et al, 2017;Yue and Unger, 2014). Our study is the first to contrast the large-scale impact of ozone and PM on global managed vegetation (crops).…”
Section: Introductionmentioning
confidence: 92%
“…They find the effect to be largest (and positive) at noontime under cloudless conditions, but less over croplands than over forests due to a lower leaf area index (LAI) in these regions. Previous studies have also looked at how ozone and/or PM impact natural vegetation and the carbon cycle, often by incorporating more advanced canopy or leaf-scale process modeling (Strada and Unger, 2016;Yue et al, 2017;Yue and Unger, 2014). Our study is the first to contrast the large-scale impact of ozone and PM on global managed vegetation (crops).…”
Section: Introductionmentioning
confidence: 92%
“…Global modelling results show that China, India and the United States are currently by far the most affected countries, bearing more than half of all global losses and threatened areas from ozone crop exposure (Teixeira et al, 2011;Sinha et al, 2015). In the USA, recent work by Yue and Unger has shown that O 3 damage decreases GPP (gross primary productivity) by 4-8 % on average in the eastern USA and leads to significant decreases of 11-17 % in east coast hotspots (Yue and Unger, 2014). Research in China has looked at the ozone exposure for rice regions, finding that regions along the Yangtze and South China regions had the highest risks in 2000, and these risks will double or triple by 2020 (Tang et al, 2014).…”
Section: Ecosystemsmentioning
confidence: 99%
“…Tang et al, 2013) and the USA (e.g. Fishman et al, 2010;Yue and Unger, 2014). To date, studies that report observed ozone values tend to be based on local sites (e.g.…”
Section: Introductionmentioning
confidence: 99%